Peran Pendidikan Kewarganegaraan dalam Menumbuhkan Sikap Toleransi di Kalangan Siswa - Nasution, Mhd Fauzi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Civic Education (Civics) is one of the educational concepts that has a strategic role in building the character of students as the next generation of the nation. One of the important values that can be developed through Civics Education is the attitude of tolerance, which is the foundation in creating harmony in a pluralistic society, ethnic, religious, racial and cultural diversity which is often a challenge in maintaining social harmony. Ignorance and prejudice can trigger conflicts that threaten national unity. This article discusses the role of Civic Education in fostering tolerance among students. The method used in this research is a literature study by reviewing various sources, such as relevant journals, books, and scientific articles. The results show that Civics Education has great potential to teach tolerance values through material approaches that emphasize diversity, equal rights, and respect for differences. Discussion-based learning, case studies, and simulations in Civics materials can encourage students to understand the importance of tolerance in everyday life. This article concludes that the integration of tolerance values in the Civics curriculum is one of the effective steps to face the challenges of intolerance in the era of globalization. Thus, tolerance education through Civics can strengthen students' awareness of the importance of maintaining diversity and social harmony.